Developing Visualization for Learning Algorithm: Decimal to Binary Visualization - Xiao, Minze; Chang, Yuan (International Journal of Educational Technology and Artificial Intelligence, 2024)
This research presents an innovative approach to visualizing the decimal to binary conversion algorithm using Adobe Animate, a versatile tool known for its animation and graphics capabilities. The Digital Dif-ferential Analyzer is a fundamental algorithm in computer graphics, and our work focuses on creating an engaging and educational visualization that demystifies its step-by-step execution. The project begins by designing algorithm that outlines the key components and stages of the decimal to binary conversion algorithm. Leveraging Adobe Animate’s user-friendly interface, we implement frame-by-frame animations that dynamically illustrate the algorithm’s progression. Each frame depicts a specific step in the conver-sion process, with of binary animation of bits. The visualization incorporates interactive elements, allow-ing users to control parameters such a decimal input. By utilizing Adobe Animate’s scripting capabilities, we enable real-time updates and dynamic conversion results, enhancing user engagement and under-standing. The inclusion of sliders, buttons, and dynamic text labels empowers users to actively manipu-late and observe the algorithm in action. Summarizing the key findings and emphasizing the importance of visualizing binary numbers in algorithm education. Encouraging educators to adopt these methods to make algorithmic concepts more accessible and enjoyable for students.